Electronic structure, stability, and magnetism of rutile-type ultrathin TiO2 nanotubes. (October 2018) - Zhang, Yongjia; Ma, Ninggui; Zhou, Min; Cao, Ensi; Sun, Li; Hao, Wentao; Yang, Zhi
Abstract: In this study, based on density functional theory, we predicted the electronic structure, stability, and magnetism of ultrathin rutile-type TiO2 nanotubes ( u -TiO2 NTs) with different curvatures. The curvature energy calculations showed that the ( m, 0) u -TiO2 NTs follow the classical elasticity theory. As the diameter of the NTs increases, the wall thickness becomes thinner, and the binding energy and band gap increase until saturation. For the (10, 0) u -TiO2 NT, the neutral Ti vacancies ( V Ti 0 ) could induce a large magnetic moment and long-range ferromagnetic coupling, whereas the neutral O vacancies ( V O 0 ) cannot. In addition to calculations of the vacancy formation energy, we investigated the magnetism and magnetic coupling of the (10, 0) u -TiO2 NT with V Ti − or V O + . We found that the introduction of V Ti − vacancies led to unstable ferromagnetic coupling in the NTs, whereas the V O + vacancies preferred to couple in a stable ferromagnetic manner. Our results suggest a possible route for obtaining high Curie temperature ferromagnetism in TiO2 materials. Highlights: Curvature energies show that ( m, 0) u -TiO2 NTs follow classical elasticity theory. Two-dimensional TiO2 nanosheet more stable than one-dimensional u -TiO2 NTs. V Ti 0 and V O + induce stable ferromagnetic coupling, whereas V O 0 and V Ti − do not. For V O +, the same types attract each other whereas different types do not.